(untitled) (Research, Society and Development, 2020)
Teachers are constantly faced with challenges related to the teaching methodology used in the classroom. Whether due to new technologies or new concepts, it is evident that teachers are reinventing themselves in an attempt to provide the best possible teaching experience to their students. This study addresses an even more challenging reality, that of carrying out all of this, however, in an environment outside the classroom. The social isolation caused by the pandemic of COVID-19 brought, abruptly, remote education to the center of attention, becoming the new reality. This article aimed to understand the differences in teaching between the public and private schools in cities in the interior of Ceará, being carried out through the application of interviews, in which the teachers’ reports were collected. While in public education the main difficulty narrated was the application of tools, in private education the greatest difficulty was to adapt the content to the methodology. In this period of remote classes, it is not only essential to train education professionals, but mainly to give voice to teachers, since they are the real transforming agents of education.